Uji Cara Aplikasi PGPR dalam Menekan Kejadian Penyakit Antraknosa pada Tanaman Cabai Hiyung di Lahan Rawa - Fahmi Rizali Cholis; Ismed Setya Budi; Mariana . (JURNAL PROTEKSI TANAMAN TROPIKA, 2021)
Chili Hiyung is a local chili variety typical of South Kalimantan. At this time began to be exposed to a lot of anthracnose disease. Control using pesticides needs to be avoided by finding more convenient control methods. Area-friendly disease control includes using PGPR (Plant Growth Promoting Rhizobacteria). The use of PGPR for chili plants in the swamp land of Hiyung village has not been studied, meanwhile its potential has been tested on several other plants. This research aims to identify the effect of PGPR in suppressing anthracnose disease in Chili Hiyung in the swamp land of Hiyung Village. The design used was a single aspect Completely Randomized Design (CRD) based on 4 (four) treatments, namely the leak, spray, or spray and leak methods. The results of the research show that the PGPR application does not affect the incidence of anthracnose disease in Hiyung chili plants in Hiyung village. But the PGPR application can increase plant size and fruit weight per branch.